2022
DOI: 10.2174/1389203723666220929105859
|View full text |Cite
|
Sign up to set email alerts
|

Glycation of Immunoglobulin-G from Pentose Sugar: A Cause for Structural Perturbations

Abstract: Background: Glycation of immunoglobulin-G (IgG) molecule with monosaccharides may cause significant structural disability thus resulting in their loss of function. The accumulation of AGEs formed from glycation play an important role in the aliments associated with metabolic diseases. Therefore, excess of sugar in plasma, interferes with the functioning of IgG and may contribute to wide range of diabetes-associated complications. The long-term formation of these heterogeneous AGEs may accumulate and can affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Accounting for glycation in immune interactions, fibrinogen was reported to induce an adaptive immune response by elevating cytokines upon its glycation 261 . Another study demonstrated that glycated immunoglobulin gamma can form IgG‐AGEs adduct and raise cellular toxicity, which may trigger various diabetic complications 262 …”
Section: Protein Glycation: Molecular Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for glycation in immune interactions, fibrinogen was reported to induce an adaptive immune response by elevating cytokines upon its glycation 261 . Another study demonstrated that glycated immunoglobulin gamma can form IgG‐AGEs adduct and raise cellular toxicity, which may trigger various diabetic complications 262 …”
Section: Protein Glycation: Molecular Insightsmentioning
confidence: 99%
“…261 Another study demonstrated that glycated immunoglobulin gamma can form IgG-AGEs adduct and raise cellular toxicity, which may trigger various diabetic complications. 262 We have reported that regular curd and yogurt (containing MG) consumption can lead to the glycation of proteins, inflammation, and oxidative stress that may cause diabetes. 139 Therefore, inhibition of this process is evolving as a practical therapeutic approach to retard aging and events of disease development.…”
Section: Protein Glycation: Molecular Insightsmentioning
confidence: 99%
“…The nextstep is to incubate the sample mixtures at physiological temperature, which is 37 • C, until the yellow mixture changes to a purple mixture. The absorbance for ketoamine detection was recorded at 525 nm wavelength, and the molar extinction coefficient of 12,640 M −1 cm −1 was used to calculate ketoamine concentration (nmol mL −1 ) [28].…”
Section: Early Glycation Detection-nitroblue Tetrazolium (Nbt) Assaymentioning
confidence: 99%